Cerebrospinal Fluid Leakage during Anterior Approach Cervical Spine Surgery for Severe Ossification of the Posterior Longitudinal Ligament: Prevention and Treatment - Lei, Tao (Orthop Surg, 2012)
OBJECTIVE: The prevention and treatment of the common complication of cerebrospinal fluid leakage (CSFL) during anterior approach cervical spine surgery for severe ossification of the posterior longitudinal ligament (OPLL) is documented. METHOD: A retrospective analysis of 47 patients with severe cervical OPLL aged 39 to 73 years (average, 56.4 years) who underwent anterior operations was conducted. All patients were classified as local or segmental types based on the thickness of the ossified mass (>5 mm) and canal stenosis rates exceeding 50%. Fifteen cases underwent discectomy and fusion and 32 cases corpectomy and fusion. Preoperative CT images were analyzed for operation breakthrough and decompression range. During surgery, the ossified mass was excised or floated and the arachnoid reserved in order to reduce dural damage. Sutures coupled with gelatin sponge or muscle pedicle were applied to repair dural defects. After surgery, patients were confined to bed to allow for drainage or puncture. RESULTS: Fifteen cases of dural defects were recognized intraoperatively. Postoperatively, 5 patients developed CSFL. Partially cut dura with intact arachnoid occurred in one patient who developed a CSF pseudocyst. No cases required secondary operations or shunt placement and all exhibited good wound healing, with JOA scores increasing from 7.30 ± 1.08 to 13.70 ± 0.81 points and improvement rates of 65.98% ± 7.35%. CONCLUSION: During anterior surgical treatment for severe OPLL, CSFL can be prevented and treated through careful analysis of CT images, meticulous operative technique, careful handling of the ossified mass, and intra‐operative repair of dural damage.